Vorogrid: A static‐aware variable‐density Voronoi mesh to design the tube structure tessellation of tall buildings. (1st September 2022) - Laccone, Francesco; Gaudioso, Domenico; Malomo, Luigi; Cignoni, Paolo; Froli, Maurizio
Abstract: In the context of tall building design, the tube concept represents one of the most performing systems. The diagrid is the widespread type of tube system and consists of a diagonal grid of beams that wraps the building, forming a diamond pattern. It performs as lateral bracing and is additionally able to sustain vertical loading through axial forces. Despite its efficiency, a growing interest is recently observed in alternative geometries to replace the diagrid pattern and improve the architectural impact conferred by the building skin aesthetics on the urban environment. The paper pursues the use of a Voronoi mesh, in which the geometry of the cells is steered to known schemes for the structural design of a cantilever tube structure. The objective is to mimic a macroscopic structural behavior through a topology and size modification of the Voronoi mesh that increases the density for creating resisting paths with higher stiffness. The paper proposes a novel method Vorogrid for designing a new class of tall buildings equipped with an organic‐looking and mechanically sound tube structure, which makes them a valuable alternative to competitors (diagrid, hexagrid, random Voronoi). Diagrids and hexagrids still remain more efficient in terms of forces and displacements but are characterized by a more usual appearance, instead Vorogrid offers more design control and better performances on average with respect to random Voronoi structures. This method is streamed into a pipeline that includes grid initialization strategies, geometric and structural optimization to mitigate the effects of the grid randomness, and structural sizing.